Synthesis of spiropyrans via the Rh(iii)-catalyzed annulation of 3-aryl-2H-benzo[b][1, 4]oxazines with diazo ketoesters. Issue 33 (6th April 2022) - Zhang, Jing Jing; Zhang, Mengying; Lu, Mingxin; He, Yuhao; Li, Song; Fan, Liangxin; Zhang, Xinle; Wu, Jia-Kai; Yang, Xifa
Abstract : An efficient Rh(iii )-catalyzed 1 : 2 coupling of 3-aryl-2 H -benzo[ b ][1, 4]oxazines with diazo ketoesters has been realized via  twofold C–H activation followed by unusual [3+3] and [4+2] annulation, providing a straightforward strategy to access polycyclic spiropyrans. Abstract : Rh(iii )-Catalyzed 1 : 2 coupling of 3-aryl-2 H -benzo[ b ][1, 4]oxazines with α-diazo-β-ketoesters has been realized for the mild synthesis of spiropyrans. The reaction proceeded via twofold C–H activation followed by unusual [3+3] and [4+2] annulation with decent functional group tolerance. Moreover, a pyranoid-skeleton intermediate was isolated as a key intermediate as a result of monoalkylation and enol oxygen annulation, which offers direct mechanistic insight.